Cardiovascular events in acute coronary syndrome patients with peripheral arterial disease treated with ticagrelor compared with clopidogrel: Data from the PLATO Trial. (June 2015) - Patel, Manesh R; Becker, Richard C; Wojdyla, Daniel M; Emanuelsson, Hakan; Hiatt, William R; Horrow, Jay; Husted, Steen; Mahaffey, Kenneth W; Steg, P Gabriel; Storey, Robert F; Wallentin, Lars; James, Stefan K
Aims: To determine the effect of ticagrelor compared to clopidogrel in patients with peripheral artery disease (PAD) and acute coronary syndromes (ACS). Methods and results: PLATO (n = 18, 624) was a multicentre, double-blind, randomized trial in ACS, that showed a 16% reduction in cardiovascular death (CV-death), myocardial infarction (MI) and stroke with ticagrelor compared with clopidogrel, without significant increase in overall major bleeding. We performed a post-hoc analysis of cardiovascular and bleeding outcomes in PLATO according to reported PAD status at baseline. At one year, CV death, MI or stroke occurred in 19.3% of patients with PAD (n = 1144) compared to 10.2% in patients without PAD ( p  < 0.001). The Kaplan-Meier one year event rate for the primary endpoint of CV death, MI or stroke in PAD patients treated with ticagrelor as compared with clopidogrel, was 18% vs 20.6% (HR: 0.85 95% CI 0.64–1.11; for PAD status by treatment interaction, p  = 0.99) and for death from any cause 8.7% vs 11.9%, (HR: 0.74 95% CI 0.50–1.08; interaction p  = 0.73). PLATO-defined major bleeding event rates at one year were 14.8% for ticagrelor compared to 17.9% for clopidogrel, (HR: 0.81 95% CI 0.59–1.10; interaction p  = 0.09). Conclusion: PAD patients have a high rate of ischaemic and bleeding events post ACS. The reduction of CV death, MI or stroke with ticagrelor compared with clopidogrel in PAD patients was consistent with the overall trial result although it did not reach statistical significance. Overall major bleeding was similar between the therapies.